2000
DOI: 10.1093/her/15.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of precontemplating smokers defined by different long-term plans to change their smoking behavior

Abstract: Abstractvariables and the quitting plans at pre-test were predictive of quitting activity after 7 months. Precontemplators who received self-help Many smokers are not motivated to quit smoking cessation materials made forward smoking. In the Stages of Change model these changes in quitting plans and these changes smokers are called precontemplators. When seemed to follow a certain order. Forward developing interventions designed to motivate changes in plans were differentially related to these smokers to quit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…The current study assessed quit intention as clinically proximal, which may elicit a desirable response in a sample that is motivated to change as compared to assessing a hypothetical, future intention to quit. Proximal plans to quit have been associated with positive outcomes in smokers who intend to quit 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The current study assessed quit intention as clinically proximal, which may elicit a desirable response in a sample that is motivated to change as compared to assessing a hypothetical, future intention to quit. Proximal plans to quit have been associated with positive outcomes in smokers who intend to quit 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy at baseline was more related to influencing diet and, above all, sun exposure. In different studies self-efficacy has been shown to be one of the best predictors of behaviors [46], including diet behavior [47]. For this reason interventions should be focused on removing barriers and providing skills to increase self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…We also report four other quit attempt outcomes and three abstinence outcomes (Table 2). Participants also completed stage of change (Prochaska & DiClemente, 1983) and self-ratings of degree of motivation (Hughes, Keely, Fagerstrom, & Callas, 2005), self-efficacy (Dijkstra & DeVries, 2000), and addiction to cigarettes . From these, we report six motivation-to-quit outcomes.…”
Section: Methodsmentioning
confidence: 99%